2020
DOI: 10.3390/ani10122336
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Characteristics, Management, and Challenges of Backyard Poultry Farming in Residential Areas of Turkey

Abstract: The aim of this study was to collect, for the first time, comprehensive information about the backyard poultry sector in Turkey. This included a profile of the poultry owners, flock characteristics, husbandry, housing conditions, the owners’ biosecurity measures and the challenges of backyard poultry farming in residential areas of Turkey. An online semi-structured survey was fully completed by 1094 respondents. The majority of respondents (91%) owned fewer than 50 birds and reported raising other poultry spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Native chicken is also preferred because it requires less feed and inputs, produces more eggs, and grows faster. Previous studies have documented that indigenous people prefer native birds because their meat and eggs are tastier, and needed for traditional ceremonial meals ( 23 , 24 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Native chicken is also preferred because it requires less feed and inputs, produces more eggs, and grows faster. Previous studies have documented that indigenous people prefer native birds because their meat and eggs are tastier, and needed for traditional ceremonial meals ( 23 , 24 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented that indigenous people prefer native birds because their meat and eggs are tastier, and needed for traditional ceremonial meals (23,24,31,32). The majority of households rear indigenous chickens for eggs and meat.…”
Section: Discussionmentioning
confidence: 99%
“…However, the difference in parasitic and ectoparasite prevalence is highly influenced by the topographic and climatic conditions, season, farm management, and the breed of birds ( Kebede-Tsegay, 2017 ). A survey carried out in the USA, where 1,482 backyard poultry flock owners were asked, showed that 11.4% had external parasite issues ( Elkhoraibi et al, 2014 ); a similar survey was also conducted on about 3,000 backyard poultry owners in Turkey, showing 14.3% of external parasites and 9.7% internal parasites ( Özdemir, 2020 ).…”
Section: Introductionmentioning
confidence: 99%